1998
DOI: 10.1016/s0014-5793(98)00451-7
|View full text |Cite
|
Sign up to set email alerts
|

A role for the signal transduction protein PII in the control of nitrate/nitrite uptake in a cyanobacterium

Abstract: In the cyanobacterium Synechococcus sp. strain PCC 7942, ammonium exerts a rapid and reversible inhibition of the nitrate and nitrite uptake, and the P ss protein (GlnB) is differentially phosphorylated depending on the intracellular N/C balance. RNA/DNA hybridizations, as well as nitrate and nitrite uptake experiments, were carried out with the wild-type strain and a P ss -null mutant. The transcriptional control by ammonium of the expression of the nir-nrtABCD-narB operon remained operative in the mutant but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
86
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(89 citation statements)
references
References 33 publications
3
86
0
Order By: Relevance
“…Cells at an arbitrary stage of growth (OD 750 = 1.5-3.0) were harvested at 7 h in the dark by centrifugation at 10,000× g for 7 min and resuspended in fresh medium. Chl a in the cyanobacteria was determined by methods reported by de Marsac and Houmard 23) .…”
Section: Methodsmentioning
confidence: 99%
“…Cells at an arbitrary stage of growth (OD 750 = 1.5-3.0) were harvested at 7 h in the dark by centrifugation at 10,000× g for 7 min and resuspended in fresh medium. Chl a in the cyanobacteria was determined by methods reported by de Marsac and Houmard 23) .…”
Section: Methodsmentioning
confidence: 99%
“…These studies also showed that the addition of l-Met sulfoximine is essential to obtain the maximal rate of nitrate consumption, which reflects the total capacity for nitrate assimilation by whole cells at a given temperature, and clearly showed that the cessation of nitrate assimilation at 15°C does not arise from the regulation of the nitrate transporter through signal transduction mediated by the P II protein (Lee at al., 1998 Hattori (1962), Synechococcus sp. PCC 6301 cells require more light to saturate, and have much greater inherent capacities for, photosynthetic oxygen evolution and carbon assimilation than for nitrate assimilation.…”
Section: Regulation Of Nitrogen and Carbon Metabolismmentioning
confidence: 98%
“…PII-null mutant studies indicate a function linked to N uptake. In an ammonium regime, dephospho-PII controls the inhibition of nitrate and nitrite uptake, whereas in the absence of ammonium, it is thought that the liganded (2-oxoglutarate being the likely effector), phosphorylated PII alleviates this inhibition (Lee et al, 1998(Lee et al, , 2000. Furthermore, a PII-null mutant demonstrated that the high-affinity bicarbonate transport system of Synechocystis PCC 6803 is under PII control (Hisbergues et al, 1999).…”
Section: Role Of Pii In Photosynthetic Bacteriamentioning
confidence: 99%